1993
DOI: 10.1111/j.1365-2214.1993.tb00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour problems in children with learning disabilities: to what extent do they exist and are they a problem?

Abstract: The parents of 68 young children with learning disabilities were interviewed to assess the number and type of behaviour problems that their child exhibited. Parents' perceptions of their ability to cope with the behaviours were sought. The average number of behaviour problems was 7.4 per child, with poor concentration and sleep problems occurring most frequently. Fifty-seven per cent of parents who reported that their child hurt themself felt unable to cope with those behaviours. Scores of parents' perceived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 3 publications
0
20
1
Order By: Relevance
“…In both the present study and that by Saxby & Morgan (1993), most of the behaviours reported by mothers were not felt by them to be definite problems. Such perceived problems represented between 3% and 5% of the total number of behaviours investigated in these studies.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In both the present study and that by Saxby & Morgan (1993), most of the behaviours reported by mothers were not felt by them to be definite problems. Such perceived problems represented between 3% and 5% of the total number of behaviours investigated in these studies.…”
Section: Discussioncontrasting
confidence: 67%
“…The average level of reported behaviours (25% in 1986/7, and 22% in 1991, out of the 54 individual behaviours investigated), compares with 28% reported by mothers in a study of 1 to 8-year-old children with intellectual disabilities (Saxby & Morgan, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…It is well-documented that children's sleep difficulties are a considerable stress factor for parents [43]. One hypothesis is that children with ADHD are more liable to wake their parents during the night than non-ADHD children, making their parents more aware of any sleep difficulties [5].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural interventions have been reported to improve mothers' mood, perceptions of their spouses, and their marriage, as well as their children's behaviour (Quine, 1992b). It has been suggested that both can affect parents' reporting of their child's behaviour (Saxby & Morgan, 1993;Sloper & Turner, 1993), possibly without any quanti able change in child behaviour. If the parents sleep better themselves, parents may have an improved mood.…”
mentioning
confidence: 99%